Recent Advances on Electrospun Nanofibers for Periodontal Regeneration - Mafalda S. Santos; Marta S. Carvalho; João C. Silva (Nanomaterials, 2023)
Periodontitis is an inflammatory infection caused by bacterial plaque accumulation that affects the periodontal tissues. Current treatments lack bioactive signals to induce tissue repair and coordinated regeneration of the periodontium, thus alternative strategies are needed to improve clinical outcomes. Electrospun nanofibers present high porosity and surface area and are able to mimic the natural extracellular matrix, which modulates cell attachment, migration, proliferation, and differentiation. Recently, several electrospun nanofibrous membranes have been fabricated with antibacterial, anti-inflammatory, and osteogenic properties, showing promising results for periodontal regeneration. Thus, this review aims to provide an overview of the current state of the art of these nanofibrous scaffolds in periodontal regeneration strategies. First, we describe the periodontal tissues and periodontitis, as well as the currently available treatments. Next, periodontal tissue engineering (TE) strategies, as promising alternatives to the current treatments, are addressed. Electrospinning is briefly explained, the characteristics of electrospun nanofibrous scaffolds are highlighted, and a detailed overview of electrospun nanofibers applied to periodontal TE is provided. Finally, current limitations and possible future developments of electrospun nanofibrous scaffolds for periodontitis treatment are also discussed.